Towards a reference genome that captures global genetic diversity - Karen H. Y. Wong (Nature Portfolio, 2020)
The human reference genome does not fully reflect human genetic diversity. Here, the authors analyse 338 human genome assemblies from diverse populations to identify missing sequences, define non-reference unique insertions and construct a Human Diversity Reference.